S15 Clinical Characteristics Of Hospitalised Patients Misdiagnosed With Community-acquired Pneumonia. (10th November 2014) - Pick, H; Lacey, J; Hodgson, D; MacDonald, E; Turvey, A; Bewick, T
Abstract : Background: The diagnosis and treatment of patients hospitalised with community-acquired pneumonia (CAP) is predicated on an acutely abnormal chest radiograph. 1 Little is known about patients who present with infective respiratory symptoms with no consolidation, who have clinically significant non-pneumonic lower respiratory tract infection (LRTI). Methods: A prospective observational cohort study of consecutive patients admitted to hospital with infective respiratory symptoms and treated for suspected CAP over winter 2013/14. Management was at the discretion of the admitting team. Results: Of 628 patients admitted to hospital during the study, 304 (48.4%) did not have acute consolidation on chest radiograph; 166 were reported as clear, and 138 as either longstanding abnormality or not acute infection. Patients with LRTI had lower admission C-reactive protein levels (median 49 mg/l vs. 85 mg/l; p < 0.01), were older (median 80.0 years vs. 76.3 years; p = 0.005), and were more likely to be managed on a non-respiratory ward (174/304 (57.2%) vs. 127/324 (39.1%); p < 0.001). A higher proportion of patients with LRTI were care home residents, although this did not reach statistical significance (56/304 (18.4%) vs. 45/324 (13.9%); p = 0.12). A microbiological diagnosis was made in only 9/304 (3.0%) patients with LRTI compared with 45/324 (13.9%) with CAP (p < 0.0001). CAP patients had a discharge clinical code of CAP (J12–18) in 247/324 (76.2%) cases; 121/304 (39.8%) patients with LRTI were miscoded as CAP. Thirty-day mortality was similar in both groups (48/324 (14.8%) vs. 43/304 (14.1%) p = 0.82), but median length of hospital stay was longer for patients with CAP (7.0 days vs. 5.6 days; p = 0.002). Conclusion: Almost half patients treated for CAP were misdiagnosed and over-treated with broad spectrum antibiotics. Patients with non-pneumonic LRTI were older, with lower C-reactive protein levels, but similar 30-day mortality. Acute respiratory illness in this group may therefore be driven by decompensated comorbidity rather than an underlying inflammatory condition; broad spectrum antibiotics may not be useful. No national guidance currently exists on the optimal management of this group, and further study is required. Reference: Lim WS et al . BTS guidelines for the management of community acquired pneumonia in adults: update 2009. Thorax 2009, 64 Suppl 3, iii1-ii55